Barbour's Bruce : A Fredome Is a Noble Thing!. - Barbour, John (Scottish Text Society, 2023)
Barbour's Bruce underpins contemporary understanding of Robert Bruce and his achievements, and sets up paradigms of medieval Scottish heroism and chivalry.